Faktor Penyebab dan Dampak Keterlambatan Pembuatan Surat Keterangan Medis untuk Klaim Asuransi di RSUD Panebahan Senopati Bantul - , PRIYANTO; , Eddy Kristiyono., A.Md.,Perkes., SKM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: File medical records in relation to the financial aspects indirectly also can be used for the replacement cost, ie the data contained therein is used as a base material or evidence of compliance with requirements for filing a claim with the insurance company by the hospital or by the patients themselves to replacement cost which has been issued to the care that has been given. Current medical records are increasingly required for billing claims to a third party in this case the insurance company concerned. But in making a claim for a company asuaransi often a delay that can be caused by several factors. Objective: The general objective of this study was to determine the delay in making Medical Certificate for insurance claims in non-governmental hospitals Panembahan Senopati Bantul. The specific objective of this research was to determine the factor of delay in the manufacture of Medical Certificate for non-government insurance claim. Methods: Descriptive qualitative approach and cross-sectional design. Research subject is the medical officer and the applicant's letter keterngan Medical Certificate for insurance claims. Object in this study is a register-making Certificate of Medical and visum et repertum. Techniques to determine the validity of the data used is triangulation of sources and techniques. Results: SKM manufacturing delay factor for insurance claims Panembahan Senopati Bantul District Hospital caused by Human Resources consisting of doctors that are difficult to be found by medical certificate officers and nurses are still often too late to return the medical record file. Manufacturing delays resulted in the applicant came before the SKM SKM for completion of insurance claims made and claims are not paid by the insurance company because the deadline for filing a claim has expired.